Anatomical and Clinical Characteristics of Paediatric and Adult Eyes - Mittal Sunita; Sharma Manisha; Mittal Kumar Sanjeev; Kumar Satish Ravi; Juneja Aarzoo; Agrawal Ajai (Wolters Kluwer Medknow Publications, 2021)
The human eye is one of the special sensory organs. Eyes undergo a series of changes right from infancy to attainment of adulthood. Major changes occur in globe dimensions, orbital and neurological structures. In order to have a sharp focus of the image on the retina, the intraocular structures undergo developmental changes in the 1st year of life along with the neurological growth which enables processing of that retinal image. The extraocular growth of the bony orbit and adnexa accompanies intraocular growth. An ophthalmologist looking after the pediatric patient must be aware of these physiological changes so as to not diagnose them as any pathologic conditions. There are few diseases which can also interfere with these normal developmental changes. It is valuable to know the developmental process to diagnose children with eye disorders. This review article lays emphasis on the normal anatomical alterations in the globe, anterior segment, pupil, lens, retina, lacrimal apparatus, and external orbit of the human eye during infancy and early adulthood and also discussing its practical implications.